The Historical Trajectory of Women’s Empowerment in Bangladesh: A Feminist Analysis (Social Science Review, 2025)
Empowerment is a popular buzzword and its meaning has evolved over time. As a concept, empowerment refers to the process of transferring power or authority to individuals, allowing them to make decisions and take control of their lives. When it comes to women’s empowerment, the meaning varies by country, but it may encompass financial autonomy, self-direction, self-confidence, and self- worth, among other aspects. To fully understand how ‘women’s empowerment’ evolved and shifted over the decades in Bangladesh, it is necessary to evaluate the historical trajectory of women’s empowerment since independence. This article critically examines earlier trends and recent interventions on women’s empowerment in Bangladesh by various stakeholders, including the government (GO) and non-governmental organisations (NGOs), from a feminist perspective. By conducting a desk review of the national discourse on women’s empowerment, the study concludes that, despite decades of interventions aimed at empowering women, there has been an overemphasis on boosting women’s financial inclusion rather than promoting women’s agency in their everyday lives. From a feminist standpoint, the study argues that, while financial inclusion for women is a prerequisite for empowerment, establishing women’s agency by allowing them to exercise their choices and decisions takes greater attention, which has long been disregarded in Bangladesh.Social Science Review, Vol. 41(2), December 2024, pp. 137-154